Doumou Douala Therapeutic Theorems for Modulo 3 Congruence Memory - Junior, Doumou Douala Mouteng Charles Valentin (Archives of Business Research, 2024)
Three mathematical theorems invented by Doumou in the medical field, aimed at curing and relieving people. Its proposition can be demonstrated by logical reasoning based on established facts or justifiable hypotheses, which is of crucial importance in the treatment of illnesses, aiming to cure them. This theorem enables the individual to find a perfect fit, a harmony between his thoughts, feelings, words and actions.